The impact of video nasal endoscopy on patient satisfaction. Issue 6 (19th February 2018) - Bhalla, Vidur; Beahm, D. David; Sykes, Kevin J.; Ndeti, Kavindu K.; Chiu, Alexander G.
Abstract : Background: Video nasal endoscopy has significant associated expense for practices, but its use has been justified by the benefit it provides to the examiner. No study has examined the perceived benefit to the patient. In this study, the impact of video endoscopy on patient satisfaction is evaluated. Methods: A prospective, randomized, single‐blinded study was performed on new patients receiving care in the rhinology clinics of a tertiary‐care center. Patients were randomized into the standard endoscopic examination (SEE) or video endoscopic examination (VEE) groups. SEE patients had their examination performed with the physician viewing the exam through the eyepiece, without a video camera, and subsequently had their examination explained. VEE patients had their examination performed with a video camera attached to the scope, recorded, and then used for the explanation. All patients were asked to complete the 22‐item Sino‐Nasal Outcome Test (SNOT‐22) and the 18‐item Patient Satisfaction Questionnaire Short‐Form (PSQ‐18). Statistical analysis was performed to identify differences between cohorts. Results: There was no significant demographic difference between groups. SNOT‐22 total and domain scores were similar between both groups ( p > 0.05). VEE patients had significantly higher general satisfaction ( p = 0.048) and communication ( p = 0.028) domains within the PSQ‐18. There was no difference between other domains ( p > 0.05). Conclusion: VEE is a valuable tool for otolaryngologists and patients. Further studies evaluating variance in patient compliance and symptomatology may provide further justification for its use.